American superrealism : Nathanael West and the politics of representation in the 1930s - Veitch, Jonathan (Madison : University of Wisconsin Press, 1997)
"Nathanael West has been hailed as "an apocalyptic writer," "a writer on the left," and "a precursor to postmodernism." But until now no critic has succeeded in fully engaging West's distinctive method of negation. In American Superrealism, Jonathan Veitch examines West's letters, short stories, screenplays and novels - some of which are discussed here for the first time - as well as West's collaboration with William Carlos Williams during their tenure as the editors of Contact. Locating West in a lively, American avant-garde tradition that sketches from Marcel Duchamp to Andy Warhol, Veitch explores the possibilities and limitations of dada and surrealism - the use of readymades, scatological humor, human machines, "exquisite corpses"--As modes of social criticism."--Jacket
Acknowledgments -- Preface -- Introduction: Who Can We Shoot? The Crisis of Representation in the 1930s -- PART I -- 1. American Superrealism -- 2. Euclid's Asshole: The Dream Life of Balsa Snell -- PART II -- 3. ""Lousy with Pure / Reeking with Stark"": Contact -- 4. The People Talk: Miss Lonelyhearts -- 5. The Folklore of Capitalism: A Cool Million -- 6. The Cliches Are Having a Ball: The Day of the Locust -- Postscript: Madonna's Bustier -- or ""The Burning of Los Angeles"" -- Notes -- Index.
Includes bibliographical references (pages 139-174) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: West, Nathanael, -- 1903-1940 -- Criticism and interpretation; West, Nathanael, -- 1903-1940; West, Nathanael; Capitalism and literature -- United States -- History -- 20th century; Politics and literature -- United States -- History -- 20th century; Literature and society -- United States -- History -- 20th century; National characteristics, American, in literature; Surrealism (Literature) -- United States; Depressions in literature; Economics in literature; Mimesis in literature; Capitalisme et littérature -- États-Unis -- Histoire -- 20e siècle.; Politique et littérature -- États-Unis -- Histoire -- 20e siècle.; Littérature et société -- États-Unis -- Histoire -- 20e siècle.; Surréalisme (Littérature) -- États-Unis.; Crises économiques dans la littérature.; Économie politique dans la littérature.; Mimêsis dans la littérature.; LITERARY CRITICISM -- American -- General; Capitalism and literature; Depressions in literature; Economics in literature; Literature and society; Mimesis in literature; National characteristics, American, in literature; Politics and literature; Surrealism (Literature); United States; 1900-1999; Electronic books; Criticism, interpretation, etc; History